On-Road Braking Performances of Semi-Metallics Brake Friction Materials Developed through Powder Metallurgy Process - Jaafar, Talib Ria; Othman, Eliasidi Abu; Selamat, Mohd Asri; Kasiran, Ramlan (Taylor's University, 2016)
Brake system is used to slow down and finally stop a motor vehicle and friction material is one of the components of the brake system. In this study, eight formulations of brake friction materials were developed through powder metallurgy processes. The samples were subjected to physical, mechanical, friction and on-road performance tests to investigate their mechanical and tribological characteristics and on-road braking performances. The data were then analysed to study the relationship between the tribological characteristics and the on-road braking performance. Test results signify that there are no simple correlations among the physical, mechanical and tribological characteristics of semi-metallic brake friction materials. It was also noticed that there are no simple correlations between the friction characteristics and road performance results. Normal and hot frictions of all the eight samples comply with requirements specified by Automotive Manufacturer Equipment Companies Agency, USA. However, on-road performance test results show that only six out of the eight formulations do comply with requirements of United Nation Economic Commission of Europe Regulation 13. Therefore, it could be concluded that on-road performance test is the ultimate measure in deciding which newly-developed formulations could be used on the road.